Alcoholism in Proverbs 23:19–21, 29–32 and the Tiv and Idoma people of Benue State - Favour C. Uroko (HTS Teologiese Studies/Theological Studies, 2023)
This article used Proverbs 23:19–21, 29–32 as a lens for analysing alcohol addiction in Benue State. The pericope warns that alcoholism leads to poverty, regrets, and life-threatening consequences. These given aphorisms listed are important in studying the growing alcohol dependency among the Tiv and Idoma people of Benue State. Alcoholism is plentiful among the Tiv and Idoma tribes, because alcoholics are found in their numbers in drinking joints and bars. Early in the morning, alcoholics leave their houses to drink with friends. Sometimes, they do not have the finance or time to take care of their families. The government seems to be overwhelmed with this challenge. Most families are unstable and children become delinquent because the father has no time to stay at home or uses money for family feeding and school fees to pay for his alcohol and those of his friends in bars and drinking joints. Unfortunately, literature on the alcoholism among the Tiv and Idoma people are scanty. Findings revealed that most Tiv and Idoma people who engage in alcoholism do so on the basis of peer pressure, depression, and the feeling that their life lacks meaning. However, Proverbs 23:19–21, 29–32 admonish men to avoid alcoholism because the dangers of alcoholism outweigh any life challenges one is going through. This is a qualitative study with data gathered from relevant academic literature. Data analysis was performed using literary analysis method and recommendations were discussed.